Sirt1/Drp1 Pathway Reduces Microvascular Endothelial Cell Injury in Diabetic Pateints’ Hearts by Inhibiting Excessive Mitochondrial Division - Huang, Shimeng; Gao, Yuanbo; Wang, Ying; Zhao, Siyu; Lu, Bing; Tao, Aibin (Current Vascular Pharmacology, 2025)
BackgroundCardiac microvessels are significantly reduced in diabetic patients, which is accompanied by a significant increase in the incidence of diabetic cardiac complications and increased mortality. This study aimed to investigate the role and possible mechanism of sirtuin 1 (Sirt1) in microvascular endothelial cell injury in diabetic hearts.MethodsType 2 diabetes mouse models and cardiac microvascular endothelial cell (CMEC) cell models were established. Cardiac microvessel density (MVD) was detected using Platelet-Endothelial Cell Adhesion Molecule 1 (CD31) immunohistochemistry. Mitochondrial reactive oxygen species (ROS) was detected with MitoSOX and morphology was observed with mitochondrial staining. CMECs angiogenesis was evaluated via scratch and angiogenesis assays. We measured cell viability with a Cell Counting Kit (CCK)-8 assay and cell injury with lactate dehydrogenase (LDH) release assay. We assessed apoptosis using TUNEL staining, Caspase-3 activity, and Western blot.ResultsThe decrease in Sirt1 protein expression was accompanied by a decrease in cardiac microvessel density in type 2 diabetic mice. After 48 h of treating the CMECs with high-glucose and palmitic acid, it was discovered that the expression of Sirt1 and dynamin-related protein 1 (Drp1) Ser637 phosphorylated protein decreased, while the expression of Cleaved Caspase-3 protein increased. Also, the angiogenesis ability of endothelial cells was decreased, while mitochondrial ROS and mitochondrial division were increased, which culminated in aggravated endothelial cell injury and increased endothelial cell apoptosis. Increased Sirt1 protein expression and function at the gene and drug levels alleviated excessive mitochondrial division, reduced apoptosis, and improved the function of CMECs by increasing the phosphorylation of Drp1 Ser637.ConclusionUnder diabetic conditions, the Sirt1/Drp1 pathway reduces injury to CMECs by inhibiting excessive mitochondrial division.
Keywords: Sirt1